Multi-sensory activities to scaffold oral fluency in English within the GRR framework in sophomore high school students during the academic year 2019 - 2020 - Muñoz Falcón, Grace Elizabeth (2020)
Implement multisensory activities within the Gradual Release of Responsibility language lesson framework when working with the content of the English curriculum to scaffold communicative oral fluency in English with sophomore high school students at Victor Manuel Guzmán during the academic year 2019 - 2020”.